Addressing conflicts of interest in Public Private Partnerships - Daar Abdallah S; Naylor Melinda; Kuziw Michael; Omobowale Emmanuel B; Singer Peter A (BMC, 2010)
Abstract Background Many articles have been written on conflicts of interests (COIs) in fields such as medicine, business, politics, public service and education. With the growing abundance of Public Private Partnerships (PPPs), often involving complex relationships among the partners, it is important to understand how COIs can be mitigated and managed in PPPs. Discussion We wanted to study PPPs, particularly in the areas of global health and agriculture, but discovered no single source of information available to identify and compare various approaches for avoiding and managing COIs in PPPs. This is a significant gap, especially for those wishing to study, compare and strengthen existing COI policies related to PPPs. In order to bridge this gap, we reviewed how PPPs currently address COIs and highlight what might be considered good practice in developing COI policies. We reviewed the online COI policies of 10 PPPs in global health and agriculture, and interviewed two global health PPP chief executives. Summary Based on our review of policies and interviews, we conclude that there exists a range of good practices including attention to accountability and governance, acknowledgement and disclosure, abstention and withdrawal, reporting and transparency, and independent monitoring. There appears to be a need for PPPs to interact closely and learn from each other on these parameters and to also place more emphasis on independent external monitoring of COIs as a means of strengthening their major social objectives on which their activities are largely predicated. We also recommend the establishment of a web based database, which would serve as a forum to discuss COI issues and how they can be resolved.